Patterns of Orthopaedic Injuries among Motorbike Accident Admissions Presenting to a Tertiary Care Hospital in Kathmandu - Banskota, B; Shrestha, S; Chaudhary, R K; Rajbhandari, T; Rijal, S; Shrestha, B K; Banskota, A K (Journal of Nepal Health Research Council, 2016)
Background: The anecdotal burden of morbidity secondary to motorbike accidents is thought to enormous by personnel involved in trauma care. The objective of the present study is to ascertain patterns and association of injuries and causes of mortality in a cohort of motorbike accident victims.Methods: A retrospective chart review of 1337 motorbike accident admissions B and B Hospital in Kathmandu between January 2009 and December 2010 was undertaken.Results: Majority of victims were between 20 to 50 years [1230 (92%) males]. Lower extremity injuries comprised on 816 (61% of total admissions). Tibia fractures were the most common injury in isolation, multiple injury, as well as polytrauma, and a vast majority of these were open fractures. Multiple injuries were seen in 82 (6.1%) patients and 33 (2.5% of Total) patients were polytraumatized. An amputation was necessary in 16 (1.2%) patients and emergent fasciotomy for compartment syndrome was necessary in 23 (1.7%) cases of tibia fractures and 39 (2.2%) of foot and ankle injuries. A floating joint injury was present in 24 (1.8%) patients.. A fat embolism syndrome (FES) was diagnosed in 8 (0.6%) patients. The overall mortality was 0.45% (6 patients). Conclusions: Motorbike accident is an important cause of morbidity and mortality in Kathmandu, and often involves a very productive age group. There is an imminent need to address this public health problem. Keywords: Accident; injury; motorbike; multiple trauma; polytrauma.